2008
DOI: 10.1016/j.soilbio.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopy for determination of various physical, chemical and biochemical properties in Mediterranean soils

Abstract: The potential of near infrared (NIR) reflectance spectroscopy to predict various physical, chemical and biochemical properties in Mediterranean soils from SE Spain was evaluated. Soil samples (n=393) were obtained by sampling thirteen locations during three years (2003-2005 period). These samples had a wide range of soil characteristics due to variations in land use, vegetation cover and specific climatic conditions. Biochemical properties also included microbial biomarkers based on phospholipid fatty acids (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
141
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(166 citation statements)
references
References 41 publications
17
141
1
7
Order By: Relevance
“…Comparing with other studies reported in the literature under laboratory measurement condition (Shepherd and Walsh, 2002;Cohen et al, 2005;Viscarra Rossel and Behrens, 2010), the model performance for pH in the prediction set is among the best models (r 2 = 0.50- (Cozzolino and Moron, 2003;Groenigen et al, 2003;Udelhoven et al, 2003;Wetterlind et al, 2010). Almost the same results as those achieved in this study were reported by Dunn et al (2002) , 2006;Zornoza et al, 2008) and CEC (r 2 = 0.13-0.90; RMSEP = 1.22-10.43 cmol kg À1 ; RPD = 0.60-2.7) (e.g. Ben-Dor and Banin, 1995;Chang et al, 2001;Awiti et al, 2008).…”
Section: Evaluation Of General Calibration Modelssupporting
confidence: 88%
See 1 more Smart Citation
“…Comparing with other studies reported in the literature under laboratory measurement condition (Shepherd and Walsh, 2002;Cohen et al, 2005;Viscarra Rossel and Behrens, 2010), the model performance for pH in the prediction set is among the best models (r 2 = 0.50- (Cozzolino and Moron, 2003;Groenigen et al, 2003;Udelhoven et al, 2003;Wetterlind et al, 2010). Almost the same results as those achieved in this study were reported by Dunn et al (2002) , 2006;Zornoza et al, 2008) and CEC (r 2 = 0.13-0.90; RMSEP = 1.22-10.43 cmol kg À1 ; RPD = 0.60-2.7) (e.g. Ben-Dor and Banin, 1995;Chang et al, 2001;Awiti et al, 2008).…”
Section: Evaluation Of General Calibration Modelssupporting
confidence: 88%
“…literature, sodium (Na ex ) and potassium (K ex ) are among the most difficult properties to be measured with the NIR spectroscopy (Malley et al, 1999;Chang et al, 2001;Zornoza et al, 2008;Pirie et al, 2005;Dunn et al, 2002;Shepherd & Walsh, 2002;Islam et al, 2003;Volkan et al, 2010;. For the same soil property, laboratory vis-NIR methods achieved higher accuracy as compared to measurement under field soil conditions, particularly with on-line vis-NIR sensors Kuang et al, 2012).…”
mentioning
confidence: 99%
“…Figure 1f shows the spectra after 1st-Der processing, and the spectral resolution is increased. There is a large fluctuation around 1650 nm and a similar result can be found in Dalal's research [5].…”
Section: Temperature and Soil Reflectancesupporting
confidence: 85%
“…Also, with the global warming, the promotion of management strategies which allow the storage of carbon in the soil and reduce emissions of carbon dioxide in the atmosphere is required [9]. In the international context, mathematical and statistical methods of prediction are increasingly tested in the soil properties analysis protocols in relation to spectroscopy data [10]- [15]. The possibility offered by spectroscopy to generate reflectance and luminance spectra in different wavelengths 250 -400 nm (ultraviolet; UV), 400 -700 nm (visible; VIS), 700 -2500 nm (near infrared; NIR), 2500 -25,000 nm (med infrared, MIR) allows an extraction of useful information about soil components at lower cost [16] [17].…”
Section: Introductionmentioning
confidence: 99%